2016
DOI: 10.1039/c6cc05910d
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional multi-recognition flexible wearable sensor via graphene aerogel printing

Abstract: Multi-response, multi-function and high integration are the critical pursuits of advanced electronic wearable sensors. Graphene aerogel endows a three-dimensional (3D) deformation morphology with excellent flexible wearable electronics of sheeted graphene. Here we report the fabrication of a neat graphene aerogel with micro extrusion printing to electronic sensor devices with a 3D nanostructure. The printed neat graphene patterns have excellent conductivity and the controllable 3D nanostructure of graphene aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 33 publications
(26 reference statements)
0
53
0
Order By: Relevance
“…Kim et al demonstrated to use 3D printing of rGO nanowires to fabricate an rGO nanoarch strain sensors. An et al demonstrated that a 3D GA‐based sensor prepared by microextrusion printing was capable of multirecognition in flexible wearable electronic sensors. Duan et al have used the 3D printing technique to prepare a 3D porous CPC for strain sensing by coating assembled CNT/rGO onto a 3D porous PDMS substrate.…”
Section: Graphene Assemblies For Electromechanical Piezoresistive Strmentioning
confidence: 99%
“…Kim et al demonstrated to use 3D printing of rGO nanowires to fabricate an rGO nanoarch strain sensors. An et al demonstrated that a 3D GA‐based sensor prepared by microextrusion printing was capable of multirecognition in flexible wearable electronic sensors. Duan et al have used the 3D printing technique to prepare a 3D porous CPC for strain sensing by coating assembled CNT/rGO onto a 3D porous PDMS substrate.…”
Section: Graphene Assemblies For Electromechanical Piezoresistive Strmentioning
confidence: 99%
“…An and coworkers [10] developed a strategy for the printing of a graphene aerogel for flexible wearable electronic sensor devices. The printed structure creates a controllable 3D porous nanostructure with excellent conductivity, which is suitable for use as a multi-recognition flexible wearable electric sensor.…”
Section: Sensor Applicationsmentioning
confidence: 99%
“…The resultant hard carbon‐aerogel‐based pressure senor showed high stability and wide detection range (50 kPa). Besides the microstructure control of the carbon aerogels, the macro‐assemblies with different patterns assisted by 3D printing is also efficient for the preparation of high‐performance carbon‐aerogel‐based strain and pressure sensors . As shown in Figure a, through 3D printing, Gao and co‐workers prepared stretchable carbon aerogels with a hierarchical structure and high retractable elongation of 200% (Figure b–f), and high fatigue resistance over 10 6 cycles.…”
Section: Aerogel‐based Sensorsmentioning
confidence: 99%